2015
DOI: 10.1002/2014wr016498
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating snow models with varying process representations for hydrological applications

Abstract: Much effort has been invested in developing snow models over several decades, resulting in a wide variety of empirical and physically based snow models. For the most part, these models are built on similar principles. The greatest differences are found in how each model parameterizes individual processes (e.g., surface albedo and snow compaction). Parameterization choices naturally span a wide range of complexities. In this study, we evaluate the performance of different snow model parameterizations for hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 54 publications
5
131
0
Order By: Relevance
“…These comparisons illustrate that forcing uncertainty cannot be discounted and that the magnitude of forcing uncertainty is a critical factor in how forcing uncertainty compares to other sources of uncertainty (e.g., structural). This resonates with the recent work of Magnusson et al (2015), who found that uncertainty in the P forcing was a greater determinant of model performance than structural considerations.…”
Section: Contextualizing Forcing and Structural Uncertaintiessupporting
confidence: 85%
“…These comparisons illustrate that forcing uncertainty cannot be discounted and that the magnitude of forcing uncertainty is a critical factor in how forcing uncertainty compares to other sources of uncertainty (e.g., structural). This resonates with the recent work of Magnusson et al (2015), who found that uncertainty in the P forcing was a greater determinant of model performance than structural considerations.…”
Section: Contextualizing Forcing and Structural Uncertaintiessupporting
confidence: 85%
“…Simulating such events is of great importance, especially for operational flood forecasting purposes. While the performance of well-calibrated models may be adequate independent of model complexity (Hock, 2003;Magnusson et al, 2015), we are particularly interested in the model performance in extreme years, when the snowmelt contribution greatly increases flood risks. This is why in the second set of modeling experiments we singled out snow-rich years as a validation data set to generate both a more challenging and more relevant test scenario.…”
Section: Model Performance Across Elevation Classes: Leave-one-out Samentioning
confidence: 99%
“…Especially at low elevations and early in the year, the DDF of M2 and M3 do not differ much and therefore produces similar runoff simulations with comparable performance. According to Lang and Braun (1990) and Magnusson et al (2015), a clearer benefit of using a flexible instead of a fixed DDF would have been expected if used within a longer time window. Third, at low elevations snowmelt may occur sporadically and not necessarily within a pre-defined season.…”
Section: Model Performance For High Elevation Catchments: Leave-one-omentioning
confidence: 99%
“…Four criterions, including The Nash-Sutcliffe efficiency coefficient (NSE) [41], correlation coefficient (R), root mean square error (RMSE) and Kling-Gupta efficiency (KGE) [42][43][44] were applied to evaluate the fitness between the simulated and observed data series of streamflow as follow:…”
Section: Hydrological Model Performance Evaluationmentioning
confidence: 99%